EVALUATION OF METHODS IN DETECTING VANCOMYCIN MIC AMONG MRSA ISOLATES AND THE CHANGES IN ACCURACY RELATED TO DIFFERENT MIC VALUES - Rossatto, Fernanda Cristina Possamai; Proença, Letícia Auler; Becker, Ana Paula; Silveira, Alessandro Conrado de Oliveira; Caierão, Juliana; D'azevedo, Pedro Alves (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
INTRODUCTION: Methicillin-Resistant Staphylococcus aureus (MRSA) presenting reduced susceptibility to vancomycin has been associated to therapeutic failure. Some methods used by clinical laboratories may not be sufficiently accurate to detect this phenotype, compromising results and the outcome of the patient. OBJECTIVES: To evaluate the performance of methods in the detection of vancomycin MIC values among clinical isolates of MRSA. MATERIAL AND METHODS: The Vancomycin Minimal Inhibitory Concentration was determined for 75 MRSA isolates from inpatients of Mãe de Deus Hospital, Porto Alegre, Brazil. The broth microdilution (BM) was used as the gold-standard technique, as well as the following methods: E-test® strips (BioMérieux), M.I.C.E® strips (Oxoid), PROBAC® commercial panel and the automated system MicroScan® (Siemens). Besides, the agar screening test was carried out with 3 µg/mL of vancomycin. RESULTS: All isolates presented MIC ≤ 2 µg/mL for BM. E-test® had higher concordance (40%) in terms of global agreement with the gold standard, and there was not statistical difference among E-test® and broth microdilution results. PROBAC® panels presented MICs, in general, lower than the gold-standard panels (58.66% major errors), while M.I.C.E.® MICs were higher (67.99% minor errors). CONCLUSIONS: For the population of MRSA in question, E-test® presented the best performance, although with a heterogeneous accuracy, depending on MIC values.